Comprehensive analysis of silicon impact on defense and metabolic responses in rice exposed to herbivory stress - Osibe, Dandy Ahamefula; Hojo, Yuko; Shinya, Tomonori; Mitani-Ueno, Namiki; Galis, Ivan (Frontiers in Plant Science, 2024)
Silicon (Si) uptake is generally beneficial for plants that need protection from insect herbivores. In pursue of mechanisms involved in Si-mediated defense, we comprehensively explored the impact of Si on several defensive and metabolic traits in rice exposed to simulated and real herbivory of Mythimna loreyi Duponchel larvae. Hydroponic experiments showed that Si-deprived rice supplemented with Si 72 h prior to insect infestation were similarly resistant to larvae as plants continuously grown in Si-containing media. Both Si and herbivory altered primary metabolism in rice, including the levels of several sugars, amino acids, and organic acids. While the accumulation of sugars was generally positively correlated with Si presence, multiple amino acids showed a negative correlation trend with Si supplementation. The levels of secondary metabolites, including isopentylamine, p-coumaroylputrescine and feruloylputrescine, were typically higher in the leaves of Si-supplemented plants exposed to herbivory stress compared to Si-deprived plants. In addition, simulated herbivory treatment in Si-supplemented plants induced more volatile emissions relative to Si-deprived plants, which was consistent with the increased transcripts of key genes involved in volatile biosynthesis. In ecological interactions, Si alone did not affect the oviposition choice of M. loreyi but gravid females showed a significant preference for simulated herbivory-treated/ Si-deprived compared to Si-supplemented plants. Our data suggest that apart from mechanical defense, Si may affect rice metabolism in multiple ways that might enhance/modulate defense responses of rice under herbivory stress.